Selection of sesame mutants for higher yield and yield contributing traits through gamma ray irradiation - Khatun, MK; Emon, RM; Bhuiyan, MSH; Malek, MA; Mahmud, SA (Bangladesh Journal of Nuclear Agriculture, 2023)
The experiment was conducted to observe their performance regarding seed yield and yield attributes, and to select promising mutant(s) having higher seed yield with shorter maturity periods. Five mutants along with the mother variety and one check variety were evaluated following a randomized complete block design with three replications at three sesame growing areas of Bangladesh during Kharif-I, 2017. Analysis of variance showed highly significant variations among the mutants and checks for most of the characters in individual locations and combined over locations. The mutant SM-07 produced the highest seed yield (1522 kg ha-1) at each location with taller plants and the shortest maturity period. The heatmap and correlation matrix showed a significant positive correlation among the no. of branch plant-1, no. of pod plant-1, and the seed yield. Considering mean seed yield over locations, three mutants viz., SM-07, SM-06 and SM-04 produced higher seed yield (1522, 1483 ,and 1461 kg ha-1, respectively) with took short days (83-85 days) to maturity. These three mutants need to be further zonal evaluation for conformity of their performance. Bangladesh J. Nuclear Agric, 37(1): 91-100, 2023